2018
DOI: 10.1152/ajpregu.00061.2018
|View full text |Cite
|
Sign up to set email alerts
|

Placental ischemia-stimulated T-helper 17 cells induce preeclampsia-associated cytolytic natural killer cells during pregnancy

Abstract: Previous studies have demonstrated that T-helper 17 (T17) cells and cytolytic natural killer (cNK) cells are increased in women with preeclampsia. In this study we investigated the role of placental ischemia-stimulated T17 cells in induction of cNK cells in pregnancy. We further assessed the role of T17 cell-mediated oxidative stress in facilitation of cNK cell activation in pregnancy by treating rats with the SOD mimetic tempol. CD4/CD25 cells were isolated from reduced uterine perfusion pressure (RUPP) rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 41 publications
(55 reference statements)
0
25
0
Order By: Relevance
“…We hypothesized that this was a result of increased ROS production, but treatment with TEMPOL had no effect on the NK cell activity (Shields et al. ). Since NK cells express the IL‐17 RC receptor and IL‐17, the major cytokine produced by T H 17 cells, is reported to be increased in PE women (Molvarec et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We hypothesized that this was a result of increased ROS production, but treatment with TEMPOL had no effect on the NK cell activity (Shields et al. ). Since NK cells express the IL‐17 RC receptor and IL‐17, the major cytokine produced by T H 17 cells, is reported to be increased in PE women (Molvarec et al.…”
Section: Discussionmentioning
confidence: 99%
“…Single‐cell suspensions of placental leukocytes were prepared, as previously described (Shields et al. ). Briefly, one placenta from each rat was homogenized and filtered through a 70‐ μ m cell strainer and resuspended in 15 mL of Rosswell Park Memorial Institute medium (RPMI) (10% FBS).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, western blot analysis performed by Ridley et al showed that KIR-3DL2 expression is regulated by NF-κB [ 71 ]. As was described before, uNKs through KIRs recognize trophoblasts; however, uNKs are generally secretory, not cytotoxic, but Shields et al showed that ischemia-induced Th17 may mediate polarization of NKs toward a cytotoxic phenotype [ 72 ]. Therefore, maybe physiological inflammation and hypoxia in uterus during placentation facilitate recognition of specific HLA by Th17, which mediate further progression of inflammation and induction of cytotoxic NKs, although this is only a hypothesis.…”
Section: Risk Factors and Genetic Ground Of Preeclampsiamentioning
confidence: 99%